Multi-directional disturbance effect of shear mechanical behaviors and fracturing mechanisms of rockmass intermittent structural plane under true triaxial shear test - Zhi Zheng; Zhanpeng Ma; Jinghua Qi; Guoshao Su; Gaoming Lu; Shufeng Pei; Quan Jiang (International Journal of Mining Science and Technology, 2025)
After the excavation of deep mining tunnels and underground caverns, the stability of surrounding rock controlled by structural planes is prone to structural damage and even engineering disasters due to three-dimensional stress redistribution and multi-directional dynamic construction interference. However, the shear mechanical behavior, fracture evolution mechanism and precursor characteristics of rockmass under true triaxial stress and multi-directional coupling disturbance are not unclear. Therefore, this study carried out true triaxial shear tests on limestone intermittent structural planes under uni-, bi- and tri-directional coupling disturbances to analyze its mechanical behavior, fracture evolution mechanism and precursor characteristics. The results show that as the disturbance direction increase, the shear strength of limestone generally decreases, while the roughness of structural planes and the degree of anisotropy generally exhibit an increasing trend. The proportion of shear cracks on the structural plane increases with the increase of shear stress. The disturbance strain rate before failure shows a U-shaped trend. Near to disturbance failure, there were more high-energy and high-amplitude acoustic emission events near the structural plane, and b-value drops rapidly below 1, while lgN/b ratio increased to above 3. These findings provide experimental recognition and theoretical support for assessing the stability of rockmass under blasting excavation.